Air-entrainment characteristics in a plunging water jet system using rectangular nozzles with rounded ends - Bagatur, T; Sekerdag, N (Water Research Commission, 2003)
When a water-jet impinges a pool of water at rest, air bubbles may be entrained and carried some way below the pool's free surface. This process is called air-entrainment or aeration by a plunging water-jet. In this study, air-entrainment characteristics such as volumetric airflow rate, air-entrainment rate, and bubble penetration depth in a plunging jet-system using inclined rectangular nozzles with rounded ends were studied depending on effective jet width at impact point. An empirical correlation for an inclined rectangular nozzle with rounded ends is presented to predict the air-entrainment rate as a function of effective jet-expansion ratio.
Keywords: Gas Entrainment